Do Attitudes Toward Violence Affect Violent Behavior?. Issue 7 (9th August 2022) - Nunes, Kevin L.; Pedneault, Chloe I.; Hermann, Chantal A.
ABSTRACT: Attitudes toward violence are important in theoretical explanations of violent behavior and efforts to reduce violent behavior. Though an association between attitudes and violent behavior has been demonstrated, most studies have used correlational/observational research designs. We conducted a randomized experiment to test the effect of attitudes toward violence on violent behavior with 285 men from the community. Participants were randomly assigned to receive material to make attitudes toward violence more negative or to a control condition. Violent behavior was then approximated by asking participants to select from a range of violent and nonviolent options in response to a series of interpersonal conflict vignettes. Participants in the negative attitude condition responded with less violence on the vignette questionnaire than did participants in the control condition (Cohen's d = −0.23, 95% CI [−0.46, 0.01]). Participants also completed a measure of attitudes toward violence at the end of the experiment; more positive attitudes toward violence showed a strong association with more violent responding on the vignette questionnaire ( r = .62, 95% bootstrapped CI [.54, .69]). Consistent with theory and practice, our findings suggest that attitudes toward violence may play a role in violent behavior.